Numerical simulation of shock-free strong compression of 1D gas layer's problem subject to conditions on characteristic - Bautin, S P; Novakovskiy, N S (Journal of physics. Conference series, 2017)
The article describes results of one-dimensional gas layers strong compression problem's math modeling. The article provided numerical algorithm for solving the one-dimensional ideal gas shock-free strong compression problem in R. Mises configuration is proposed too. The method combines finite-difference method ROMB and tracking feature method. The method allows to calculate gas-dynamic characteristic (velocity, density, etc.) of ideal gas layer while time increase and provides better accuracy in comparison with other finite-difference method. The accuracy of the proposed method was demonstrated in calculations of test plane-symmetry problem. Exact solution and numerical one agree quite well. Numerical results of solving one-dimensional problems with different symmetry and gas characteristic is also shown. The main results of numerical simulations are shown in graphs and tables.